Impact of milling on zinc retention in maize and its implication on zinc trait prioritization - Taleon, Victor; Palacios-Rojas, Natalia; Dollah, Yusuf; Menkir, Abebe (2024)
High kernel-zinc maize (HKZM) has the potential to alleviate zinc deficiency in regions with high maize consumption, particularly in Sub-Saharan Africa. However, milling HKZM can lead to loss of zinc when removing the pericarp and embryo. This study evaluated the zinc distribution in kernel components of HKZM and examined how commercial milling affected zinc concentration in maize flour produced in Nigeria and Malawi. The zinc concentration in HKZM lines ranged 27.0–30.7 µg g-1 while in conventional maize it ranged 19.5–22.6 µg g-1. Zinc in the endosperm represented 19.9–27.5% of the total kernel zinc while that in the embryo represented 66.3–73.3%. Environmental factors had a significant effect on kernel zinc concentrations. In both Nigeria and Malawi, maize grain from commercial mills had 21 µg g-1 zinc. Zinc losses during dehulling and degerming was 22–65% in Nigeria and 32–84% in Malawi, resulting in retention of 6–10 µg g-1 and 4–18 µg g-1, respectively. While HKZM shows promise in alleviating zinc deficiency, its anticipated impact may be limited in regions where refined maize is used for making foods. Therefore, the zinc concentration in milled grain should be explored as a potential trait instead of zinc in the whole grain and its priority revisited, for TPPS of market segments that frequently use dehulled and degermed maize.